PENGARUH DIGITAL MARKETING, VARIASI PRODUK, BRAND IMAGE TERHADAP LOYALITAS NASABAH MELALUI KEPUASAN NASABAH PT. PEGADAIAN AREA MALANG - Aditya, I Nyoman (Jurnal Manajerial Bisnis, 2025)
Customer loyalty is very important for companies, because retaining means improving financial performance and company survival. Customer satisfaction is important to maintain and strengthen brand-customer relationships. This research aims to describe and determine the influence of Digital Marketing, Product Variations, Brand Image on Customer Loyalty Through Customer Satisfaction at PT Pegadaian Area Malang. The sample used in this research was 100 respondents using cluster sampling technique. This research uses quantitative data in the form of primary data sources with survey data collection techniques using questionnaires. The data collection method uses a five-point Likert Scale. This research uses two-way linear regression analysis with the help of SmartPLS. The results of simple linear regression analysis show that Digital Marketing has an indirect effect on customer loyalty through customer satisfaction, Product Variations product variations have an indirect effect on customer loyalty through customer satisfaction, Brand Image has an indirect effect on customer loyalty through customer satisfaction, while satisfaction customers have no influence on customer loyalty at PT Pegadaian Area Malang.